2016
DOI: 10.1159/000445437
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-Induced Death of Human Haematological Malignant Cell Lines Is Independent of TRPV1 Activation

Abstract: The effect of the plant-derived vanilloid, capsaicin (CAP), on the metabolic activity of THP-1, U266B1 and U937 hematological malignancy cells was determined. CAP reduced metabolic activity in a concentration-dependent manner in the three cell lines. A biphasic effect was observed on THP-1 cells (EC50: IC50 (95% CI) 32.9 (19.9-54.3)/219 (144-246) µmol/l). U266B1 cells were more resistant to CAP than THP-1 and U937. Metabolic activity was significantly inhibited by CAP in U937 compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…TRPV1 antagonists, in addition to blocking the TRPV1 channel, exhibit different biological activities; for example, AMG517 causes hyperthermia [42], AMG9810 promotes mouse skin tumorigenesis [43], and capsazepine induces colorectal cancer apoptosis [44]. It was previously unclear whether capsaicin analogues could induce apoptosis via TRPV1dependent pathways [45,46]. Taken together, our results (i.e., TRPV1 antagonist capsazepine enhanced hyperthermia-induced apoptosis) support this hypothesis.…”
Section: Discussionsupporting
confidence: 74%
“…TRPV1 antagonists, in addition to blocking the TRPV1 channel, exhibit different biological activities; for example, AMG517 causes hyperthermia [42], AMG9810 promotes mouse skin tumorigenesis [43], and capsazepine induces colorectal cancer apoptosis [44]. It was previously unclear whether capsaicin analogues could induce apoptosis via TRPV1dependent pathways [45,46]. Taken together, our results (i.e., TRPV1 antagonist capsazepine enhanced hyperthermia-induced apoptosis) support this hypothesis.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast to the results from sciatic nerve, in the small intestine, the increase of F4/80 macrophages did not correlate proportionally with an increase of the TRPV1 receptor expression in the small intestine. This suggests a further TRPV1-independent effect of capsaicin which was described recently [ 58 , 59 ] and should be investigated in further studies. The pathways of p38 MAPK and MAPKAPK2 (MK2) are particularly interesting, because of their expression in immune cells.…”
Section: Discussionsupporting
confidence: 68%
“…Of note, some studies have revealed that the effect of capsaicin was TRPV1 independent. For example, capsaicin was able to induce the death of cancer cells by activating the TRPV6 or CB1 channel (Lau et al, 2014;Omari et al, 2016). Therefore, alternative targets may also be involved in mediating the proapoptotic effect of capsaicin in melanoma, which needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%